1977
DOI: 10.1016/s0010-9452(77)80024-5
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Memory in Patients with Anterior Temporal Lobectomy

Abstract: Right and left temporal lobectomy patients, matched in age and intelligence, made more errors in odor recall than a control group. Patients with right temporal lobe excisions recalled significantly fewer odors correctly than patients with left temporal lobe excisions. Olfactory memory scores were not related to other memory deficits associated with left or right temporal lobe dysfunction or to intelligence or lesion size. However, in patients with right temporal lobectomy, percent of odors recalled correctly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 11 publications
6
38
0
Order By: Relevance
“…Several authors have reported findings suggesting that right temporal-lobe or orbitofrontallesions lead to more marked deficits than do similar lesions in the left hemisphere in odor matching or recognition tasks (Abraham & Mathai, 1983;Jones-Gotman & Zatorre, 1988a;Rausch, Serafetinides, & Crandall, 1977). On the other hand, neither Eskenazi and colleagues (Eskenazi, Cain, Novelly, & Friend, 1983;Eskenazi et al, 1986) nor Jones-Gotman and Zatorre (l988b) reported significant differences related to side of excision in several other 01-factory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported findings suggesting that right temporal-lobe or orbitofrontallesions lead to more marked deficits than do similar lesions in the left hemisphere in odor matching or recognition tasks (Abraham & Mathai, 1983;Jones-Gotman & Zatorre, 1988a;Rausch, Serafetinides, & Crandall, 1977). On the other hand, neither Eskenazi and colleagues (Eskenazi, Cain, Novelly, & Friend, 1983;Eskenazi et al, 1986) nor Jones-Gotman and Zatorre (l988b) reported significant differences related to side of excision in several other 01-factory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies on the effects of lateralized temporal lobe damage on odor memory, however, have been mixed, with some work showing a specific impairment following right temporal lobectomy (Rausch et al 1977), but other studies showing equivalent impairment in left and right sided lobectomy patients (Henkin et al 1977;Eskenazi et al 1983Eskenazi et al , 1986Dade et al 2002). Most recently, Dade et al (2002) have shown that both right and left-sided temporal lobectomy patients are equally impaired in an odor recognition paradigm including three different condtions, (1) after a single odor exposure, (2) after four odor exposures, and (3) after a 24-h delay interval.…”
Section: Olfactory Memory Following Amygdala Damagementioning
confidence: 99%
“…Some authors have suggested a preferential role of the right temporal cortex in olfactory memory (Rausch et al 1977)-in line with a material-specific advantage of the left hemisphere for verbal memory and the right hemisphere for nonverbal memory (Dobbins et al 1998;Buchanan et al 2001). In contrast, Henkin and colleagues described a study in which left temporal excision resulted in greater impairment in olfactory recognition than did right-sided damage (Henkin et al 1977).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal damage also compromises olfactory discrimination in rats, but only if the task includes the simultaneous presentation of two stimuli (5)(6)(7)26). Human studies have indicated that patients with focal brain lesions involving orbitofrontal (21,28,37) or anterior temporal cortex (8,10,21,30,37) are impaired on odor identification and discrimination tasks. In contrast, those patients with cortical lesions confined to occipital or parietal regions demonstrate intact olfactory abilities (37).…”
Section: Alcoholmentioning
confidence: 99%